Which Predicts Quadriceps Muscle Strength in Knee Osteoarthritis: Biological Markers or Clinical Variables? - Neslihan GÖKÇEN,; Sibel BAŞARAN,; İlke Coşkun BENLİDAYI,; Çiğdem ÖZDEMİR,; Gülşah SEYDAOĞLU, (Archives of Rheumatology, 2017)
Objectives: This study aims to evaluate the relationship between biological markers and quadriceps muscle strength, the correlation of clinical variables with quadriceps muscle strength, and the results according to the radiological severity in patients with knee osteoarthritis. Patients and methods: A total of 152 patients (22 males, 130 females; mean age 57.3±7.5 years; range 40 to 70 years) with primary knee osteoarthritis were included in the study. We evaluated biological markers of C-telopeptide of type I collagen, C-telopeptide of type II collagen, leptin, and osteocalcin along with 25-hydroxy vitamin D. We measured quadriceps muscle strength both by manual muscle tester and computerized isokinetic dynamometer. We evaluated pain and functional status of the patients by visual analog scale and Western Ontario and McMaster Universities Osteoarthritis Index. We analyzed the correlation between biological markers and quadriceps muscle strength along with clinical variables. We classified the strength of correlations as no-very weak, weak-moderate, moderate-strong, and excellent. Results: Of the patients, 76.9% (n=117) were obese. Quadriceps muscle strength measures were significantly lower in females than that in males. There was no-very weak correlation between biological marker levels and quadriceps muscle strength. However, weak-moderate correlations were found between clinical variables (pain and Western Ontario and McMaster Universities Osteoarthritis Index scores) and quadriceps muscle strength measures. Conclusion: Among the measured biological markers, none had any influence on quadriceps muscle strength in patients with knee osteoarthritis. However, pain and functional status of the patients might affect quadriceps muscle strength.